THE DESCRIPTION OF STRESS LEVELS OF PARENTS ACCOMPANYING CHILDREN STUDY FROM HOME (SFH) DURING THE COVID-19 PANDEMIC - Feri Catur Yuliani; Erlina Hermawati; Ahda Maulida Ulufan Nurinnafi’a (Jurnal Keperawatan Respati Yogyakarta, 2022)
The current case of the spread of Covid-19 in Indonesia is still very massive, the Ministry of Education and Culture issued a policy for learning activities to be carried out from home. During the implementation of learning from home, it turns out that there are many obstacles that are felt by educators and parents so that it triggers stress on parents. The purpose of this study was to determine the results of parents' stress levels which could be a consideration for educators to choose the right method when carrying out learning from home according to the abilities of their parents. This type of research is descriptive with a quantitative approach. Descriptive analysis is data analysis by describing or describing the data that has been collected. The sampling technique used was consecutive sampling with a sample of 717 respondents and data collection by questionnaires containing identity, informed consent, and Perceived Stress Scale (PSS) questionnaires. The results of The Description of Stress Levels of Parents Accompanying Children Study From Home (SFH) during the Covid-19 Pandemic showed that 8% of respondents experienced severe stress, 75% experienced moderate stress, and 16% experienced mild stress.